2021
DOI: 10.1039/d0sm01299h
|View full text |Cite
|
Sign up to set email alerts
|

Structural, mechanical, and biological characterization of hierarchical nanofibrous Fmoc-phenylalanine-valine hydrogels for 3D culture of differentiated and mesenchymal stem cells

Abstract: Fmoc-dipeptides are a class of short aromatic peptides featuring eminent supramolecular self-assembly, which is due to aromaticity of the Fmoc group that improves the association of peptide building blocks. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The effect of Fmoc-RGD as a cell–matrix adhesion molecule was investigated by preparing Fmoc-FF hydrogels containing WJ-MSCs with various contents of Fmoc-RGD or the control sequence (Fmoc-RGE). WJ-MSCs were isolated, expanded, and characterized according to our previous report [ 25 ]. For cell encapsulation, a mixture containing an equal volume of Fmoc-dipeptide solution with cell suspensions was prepared in serum-free DMEM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of Fmoc-RGD as a cell–matrix adhesion molecule was investigated by preparing Fmoc-FF hydrogels containing WJ-MSCs with various contents of Fmoc-RGD or the control sequence (Fmoc-RGE). WJ-MSCs were isolated, expanded, and characterized according to our previous report [ 25 ]. For cell encapsulation, a mixture containing an equal volume of Fmoc-dipeptide solution with cell suspensions was prepared in serum-free DMEM.…”
Section: Resultsmentioning
confidence: 99%
“…Fmoc-FF (Chempep, USA) was synthesized through tert-butyl ester reaction chemistry, as reported elsewhere [ 25 ]. Briefly, 315 µl isobutyl chloroformate was added to the Fmoc-phenylalanine-OH (472 mg) solution in CHCl 3 under stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Field Emission SEM Studies with the LP2 Peptide. To further visualize the supramolecular nanoscale morphology of assemblies of the LP2 peptide, field emission scanning electron microscopy (FESEM) studies 25,26 were performed with the LP2 peptide in Milli-Q water and images were captured. Prominent nano-globular assemblies of the LP2 were visible (Figure 3E).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Over the years, as more and more Fmoc-modified dipeptide hydrogelators were reported, such as Fmoc-Phe-Tyr ( Wang et al, 2008 ; Sadownik et al, 2011 ; Hughes et al, 2013 ), Fmoc-Phe-Leu ( Ren et al, 2020 ), Fmoc-Phe-Cys ( Wang and Chau, 2012 ), Fmoc-Phe-Val ( Najafi et al, 2021 ), Fmoc-Tyr-Ala ( Bai et al, 2014 ; Ren et al, 2020 ), Fmoc-Tyr-Ser ( Hughes et al, 2012 , 2013 ; Bai et al, 2014 ), Fmoc-Tyr-Thr ( Hughes et al, 2012 , 2013 ), Fmoc-Tyr-Asn ( Hughes et al, 2013 ), and Fmoc-Gly-Ser, which also self-assembled into fibrillar structures like Fmoc-Phe-Phe, the results indicated that the π–π and hydrophobic interactions of intermolecular Fmoc groups are the main driving forces in the self-assembly process of these systems. Moreover, double Fmoc group-containing dipeptide, Fmoc-Lys (Fmoc)-Asp, as an hydrogelator with the lowest CGC ever reported, 0.002 wt% (28.3 × 10 –6 M), was reported by Gazit and Wei et al ( Chakraborty et al, 2020 ).…”
Section: Cooh-terminal and N-terminal Modified Dipeptidementioning
confidence: 99%